Individuals Age Determination from Human Dental Pulp Through DNA Analysis by PCR - Tejasvi, M.L. Avinash; CK, Anulekha Avinash; Reddy, E. Rajendra; Kulkarni, Pavan; Bhayya, Harsha; Kugaji, Manohar S. (Global Medical Genetics, 2021)
Objectives Age estimation in forensic odontology is having a great importance in recent times because of the request by court or other government authorities so that immigrants whose real age is unknown should not suffer unfair disadvantages because of their supposed age, and so that all legal procedures to which an individual's age is relevant can be properly followed.Purpose The present study was planned to be conducted on pulp tissue and dental hard tissues derived from individuals for DNA isolation and age determination .Materials and Methods The present study was an experimental single-blinded study consisting of 30 extracted teeth categorized into three groups as follows: Group A: 10 to 20 years, Group B: 21 to 30 years, Group C: 31 to 40 years. DNA was isolated from the pulp of each tooth and quantitative polymerase chain reaction (qPCR) for calculating telomere length was performed.Results With increase in age, the length of telomere gets shortened which will be helpful in analyzing the age of the person when morphological and biological remnants are not available except the tooth.Conclusion The present study found that estimation of human age based on the relative TL measured by the real-time quantitative PCR may be a useful method for age prediction, especially when there is no morphologic information in the biological sample. This is the first study to accesses the age of a person by telomere length using dental pulp.
Keywords: age; PCR; pulp; dentin